Analisa Studi Empirik Kerangka Kerja Pengukuran Kualitas Perangkat Lunak Bebas Cacat - Agus Pamuji (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Testing activitiy is a strategic step to determine software quality was generated,  so that is accepted by the end user. In the testing an errors  were found that may be cause to risk a defect on the software. This study was conducted by establishing a measurement framework to analyze software metrics test toward risk prediction of defects consisting of defect density, defect removal, and Line of code. In the analysis, the data set contains 53 module samples through a statistical approach with correlation analysis techniques. Based on the hypothesis were proposed, that there are only 2 of 3 items is received and shows a high significance of defect density and removal of defects towards software quality measurement.